2016
DOI: 10.1038/ejcn.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity effect of Pediococcus pentosaceus LP28 on overweight subjects: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Heat-killed LP28 displays an antiobesity effect that reduces BMI, body fat and waist circumference, suggesting that the plant-derived lactic acid bacterium LP28 would be a promising preventive of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 27 publications
3
77
0
3
Order By: Relevance
“…Of the 26 articles which were full text screened, a total of 11 articles did not meet the criteria of inclusion either because the independent effects of probiotics on outcomes were not possible to estimate (23)(24)(25)(26)(27)(28)(29)(30), the probiotic species were not defined (31) or the patients had undergone gastric bypass (32) or lacked sufficient information on the outcomes of interest (33). Finally, 15 articles were included in the systematic review and meta-analysis (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 26 articles which were full text screened, a total of 11 articles did not meet the criteria of inclusion either because the independent effects of probiotics on outcomes were not possible to estimate (23)(24)(25)(26)(27)(28)(29)(30), the probiotic species were not defined (31) or the patients had undergone gastric bypass (32) or lacked sufficient information on the outcomes of interest (33). Finally, 15 articles were included in the systematic review and meta-analysis (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Study Selectionmentioning
confidence: 99%
“…The majority of the studies reported changes, or baseline and final values, of body weight (n = 13), BMI (n = 13) or both (n = 10), whereas 7 and 5 studies reported changes or baseline and final values of fat mass and fat percentage, respectively. Changes in body weight, BMI, fat mass/fat percentage or related outcomes such as changes in abdominal fat mass were the primary outcomes in 9 of the included studies (35)(36)(37)39,40,(42)(43)(44)(45).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…6) Furthermore, the strain is also useful to reduce body fat and body weight in human clinical study. 3) In the present study, EPSs produced by the both LY45 and PY45 strains were shown to inhibit the activity of hyaluronidase, which contributes to early inflammatory reactions. In addition, we chemically characterized the EPSs produced by two thermophilic LAB strains.…”
mentioning
confidence: 99%
“…We have demonstrated that some strains stocked in the LAB library are useful for enhancing intestinal immunity, improving liver function, and preventing metabolic syndrome. [3][4][5][6] LAB fermentation often proceeds even at low temperatures, causing the overgrowth of LABs. As the result, the degradation of flavors is proceeded and affected with taste of the fermented foods.…”
mentioning
confidence: 99%
“…Recently, this strain was used in a clinical trial confirming the results obtained in the murine study. Furthermore, LP28 heat-killed cells display an anti-obesity effect that reduces BMI, body fat, and waist circumference, indicating that the LP28 strain represents a candidate for metabolic syndrome prevention/treatment [159]. …”
Section: Reviewmentioning
confidence: 99%